'I can't breathe': the biopolitics and necropolitics of breath during 2020. (2nd October 2021) - Hristova, Stefka; Howard, Amy L.
ABSTRACT: In the United States, 2020 was defined by mortality: the COVID-19 health pandemic on the one hand and by a racist pandemic (or a lasting endemic) on the other. In both pandemics, the phrase 'I can't breathe' emerged as emblematic of these multifaceted crises. Within the United States, each pandemic was perceived and articulated quite differently by centrist and right-wing political ideologies. This article was stimulated by a political cartoon created by Nick Anderson. The diptych presents two scenes: one, symbolising Black Americaand a second representing White America . In examining the various attitudes towards the deadly health and racism crises, we outline four distinct approaches towards the understanding of biopower, sovereignty and the social contracts employed by each event. These approaches centre around issues of biopolitics and necropolitics. Whose breath 'counts' is in question here. Through social media analysis, we detail the mechanisms through which activism and its neutralisation were carried out and how the plea of 'I can't breathe' became the politicised slogan for those who refused to limit economic activity, wear masks and curb social liberties to prevent the spread of the virus.